A new approach to evaluating entrepreneurial opportunities. Issue 1 (12th June 2018) - Adel Rastkhiz, Seyedeh Elahe; Mobini Dehkordi, Ali; Yadollahi Farsi, Jahangir; Azar, Adel
Abstract : Purpose: In order to answer which opportunities are better to pursue, the purpose of this paper is to propose and empirically test a decision-making model for evaluating and selecting entrepreneurial opportunities. Design/methodology/approach: First, the authors identified common evaluation criteria through a systematic review of 45 high quality articles published in top entrepreneurship and management journals between 2000 and 2017. Second, fuzzy screening technique has been employed to offer the decision-making model. Third, the authors used data of six evaluations provided by five experts at a medium-sized biotech firm to test the model. Findings: The study shows that common decision criteria for evaluating entrepreneurial opportunities fall into seven categories. According to these criteria and using fuzzy screening technique, a multi-expert multi-criteria decision-making (ME–MCDM) model has been suggested for evaluating and selecting opportunities. Practical implications: This model can be served in situations in which decision makers should select a small number of opportunities among the larger set with regard to opportunity profile and minimal information. More opportunities and more decision makers can be included in the model. When the number of opportunities and decision makers are high, it is possible to use programming for fast, accurate and easy calculation. Originality/value: This study is the first systematic review of opportunity evaluation criteria. It is also the first considering opportunity evaluation as a multi-expert decision-making process.